Computational systems biology - Eils, Roland; Kriete, Andres (Amsterdam Elsevier/AP, 2014)
This comprehensively revised second edition of Computational Systems Biology discusses the experimental and theoretical foundations of the function of biological systems at the molecular, cellular or organismal level over temporal and spatial scales, as systems biology advances to provide clinical solutions to complex medical problems. In particular the work focuses on the engineering of biological systems and network modeling.Logical information flow aids understanding of basic building blocks of life through disease phenotypes.
Introducing Computational Systems Biology Roland Eils and Andres Kriete -- Structural Systems Biology: Modeling Interactions and Networks for Systems Studies Robert B. Russell ... [et al.] -- Understanding Principles of the Dynamic Biochemical Networks of Life Through Systems Biology Hans V. Westerhoff ... [et al.] -- Biological Foundations of Signal Transduction, Systems Biology and Aberrations in Disease Ursula Klingmèuller ... [et al.] -- Complexities in Quantitative Systems Analysis of Signaling Networks Christina Kiel and Luis Serrano -- Gene Networks: Estimation, Modeling, and Simulation Seiya Imoto, Hiroshi Matsuno and Satoru Miyano -- Reconstruction of Metabolic Network from Genome Information and its Structural and Functional Analysis Hong-Wu Ma and An-Ping Zeng -- Standards, Platforms, and Applications Stanley Gu and Herbert Sauro -- Databases, Standards, and Modeling Platforms for Systems Biology Juergen Eilsa ... [et al.] -- Computational Models for Circadian Rhythms: Deterministic versus Stochastic Approaches Jean-Christophe Leloup, Didier Gonze and Albert Goldbeter -- Top-Down Dynamical Modeling of Molecular Regulatory Networks Reinhard Laubenbacher and Pedro Mendes -- Discrete Gene Network Models for Understanding Multicellularity and Cell Reprogramming: From Network Structure to Attractor Landscapes Landscape Joseph Xu Zhou ... [et al.] -- Stochastic Simulations of Cellular Processes: From Single Cells to Colonies John Cole ... [et al.] -- Advances in Machine Learning for Processing and Comparison of Metagenomic Data Jean-Luc Bouchot ... [et al.] -- Systems Biology of Infectious Diseases and Vaccines Helder I Nakaya -- Computational Modeling and Simulation of Animal Early Embryogenesis with the MecaGen Platform Julien Delile, Renâe Doursat and Nadine Peyriâeras -- Developing a Systems Biology of Aging Andres Kriete and Mathieu Cloutier -- Molecular Correlates of Morphometric Subtypes in Glioblastoma Multiforme Hang Chang ... [et al.] -- Applications in Cancer Research: Mathematical Models of Apoptosis Stefan M. Kallenberger, Stefan Legewie and Roland Eils.
Includes bibliographical references and indexes.
Keywords: Biological systems -- Computer simulation; Systems biology; Computational Biology; Systems Biology; Electronic books